Application of Participatory Leadership in Optimizing the Potential of the Agricultural Sector in Gorontalo Regency - Putra, Hasrul Eka; Marzaman, Atika (Gorontalo Journal of Government and Political Studies, 2019)
Agriculture is the most important sector in economic development and fulfillment of public welfare. By looking at the urgency of the agricultural sector, this study will explore information about the application of participatory leadership in Gorontalo Regency, namely through the process of community involvement and empowerment in order to maximize the potential of the agricultural sector.Research will be conducted with qualitative methods with data collection techniques through: interviews and literature review. Data obtained regarding agricultural potential in Gorontalo Regency along with the problems and constraints faced are then used to maximize participatory leadership to increase the potential of the agricultural sector.The results of this study explain that Gorontalo District has enormous agricultural potential when viewed from the area of land and the livelihood of its people. For this reason, active involvement of all relevant stakeholders, especially the regional government, is needed. Regional leaders in this case the village head and village head must prioritize community involvement in the agricultural policy making process. From the results of the research conducted, it was found that in the smallest level of government, in this case the village, musrembangdes in fact did not run optimally. As a result the policy was only implemented by the government where only a small proportion of the community were involved in the policy formulation process and tended not to be involved in the implementation process and oversight of its policies. The results of this study will certainly be input for local governments to conduct re-evaluations in the process of community participation and leadership processes so as to be able to support the progress of the regional agricultural sector.